Sequential development of multifocal recurrent non-Hodgkin's lymphoma of mucosa-associated lymphoid tissue and diffuse large B-Cell lymphoma in a single patient: A case report. Issue 21 (May 2018) - Yang, Xubo; Min, Xiaoxue; He, Weimin
Abstract: Rationale: Diffuse large B-cell lymphoma (DLBCL) and extranodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue (MALT) belong to Non-Hodgkin's lymphoma (NHL). DLBCL rarely involves the orbit. MALT lymphomas, which account for 8.0% of NHLs, rarely involve parotid gland, trachea and bronchus. Patient concerns: We present a rare case of a long-surviving patient (≥10 years) with sequential development of multifocal recurrent non-Hodgkin's lymphoma of mucosa-associated lymphoid tissue (MALT) and diffuse large B-Cell lymphoma (DLBCL). In August 2007, a 41-year-old man developed MALT lymphoma in the parotid gland and local irradiation was administered. In July 2008, he exhibited systemic multifocal lymphadenopathy and was diagnosed with DLBCL. He received standard combination chemotherapy and autologous hematopoietic stem cell transplantation. He was well until February 2013 when he developed MALT lymphoma of the bronchus. Subsequently, he received standard combination chemotherapy. In November 2013, the patient had a relapse of the MALT lymphoma by tracheal biopsy and received local radiation. He was well until March 2015 when he developed a MALT lymphoma of the left thigh. He underwent surgery, local irradiation and rituximab monotherapy. In September 2015, surgical resection of the left orbital masses was performed, and the biopsy revealed the presence of DLBCL. One month later, lymphadenopathy was palpated in the neck, the lower left region of the umbilicus, and the left calf. Then he received chemotherapy with rituximab and lenalidomide. In March 2016, the patient underwent surgical resection for a right popliteal mass, and the resection biopsy revealed DLBCL. To date, the patient is still alive. Diagnoses: The patient was diagnosed as multifocal recurrent MALT and DLBCL. Interventions: Repeated positron emission tomography-computed tomography (CT) and biopsy were performed. Outcomes: CT and biopsy revealed sequential development of multifocal recurrent NHLs of MALT lymphoma and DLBCL. The correlation between MALT and DLBCL may represent a Richter transformation. Standard treatments, such as combination chemotherapy, autologous hematopoietic stem cell transplantation, and irradiation, may be driving factors for phenotypic changes in neoplastic cells. Lessons: Physicians should pay particular attention to the long-term development of other types of NHL after achieving complete remission of one type of NHL.